Association study between the neurexin‐1 gene and tardive dyskinesia. (January 2017) - Lanning, Rachel; Lett, Tristram A.; Tiwari, Arun K.; Brandl, Eva J.; de Luca, Vincenzo; Voineskos, Aristotle N.; Potkin, Steven G.; Lieberman, Jeffrey A.; Meltzer, Herbert Y.; Müller, Daniel J.; Remington, Gary; Kennedy, James L.; et al.
Abstract: Objective: Tardive dyskinesia (TD) is a motor side effect that may develop after long‐term antipsychotic treatment. Schizophrenia has recently been associated with the Neurexin‐1 ( NRXN1 ) gene that codes for a cell adhesion molecule in synaptic communication. Methods: This study examined five NRXN1 single‐nucleotide polymorphisms (SNPs) for possible association with the occurrence and severity of TD in 178 schizophrenia patients of European ancestry. Results: We did not find these SNPs to be significantly associated with TD. Conclusions: More research is needed with additional SNPs and in bigger samples before we can completely rule out the role of NRXN1 in TD.